EVALUASI PROGRAM DIKLAT PRAJABATAN CPNS GOLONGAN I DAN II DI PUSDIKLAT BMKG (Studi Evaluatif Menggunakan Model Kirkpatrick) - Malik, Asep Jamaludin (Pusdiklat BMKG, 2019)
This study focuses on investigating the effectiveness in enforcing Education and Training Program of Prepositioned First and Second Level Civil Servant Candidates (CPNS) in Education and Training Center of Meteorology, Climatology and Geophysics Department using the 4-level evaluation model developed by Kirkpatrick which includes reaction, learning, behavior and result. Instruments of data collection includes observation, questionnaires, interviews and documentation studies. Reaction evaluation measures the participants’ satisfaction towards implementation of the enforcement of Education and Training Program for The First and Second Level Civil Servant Candidates (CPNS) using ANEKA patterns, whereby high level of satisfaction can motivate the participants to complete the training. Learning evaluation assess the participants’ ability in truly understanding the given training materials and subsequently apply the knowledge in actualization activities. Behavior evaluation measures the positive behavioral changes among the participants in carrying out task given to their units while implementing the basic values of civil servant profession. Results evaluation determines the impact of the training in improving the performance and productivity of the participants upon training completion.